EFEK ANTIPIRETIK EKSTRAK DAUN PALIASA (Kleinhovia hospita L.) TERHADAP TIKUS PUTIH JANTAN (Rattus norvegicus L.) YANG DIINDUKSI VAKSIN DIFTERI PERTUSIS TETANUS - Shella Desiana; Yuliet Yuliet; Ihwan Ihwan (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Paliasa (Kleinhovia hospita L.) is a plant that is empirically used as a fever-lowering drugs. Antipyretic activity test Paliasa leaf ethanol extract of the white male rats (Rattus norvegicus) aims to determine the effect of the antipyretic effect of ethanol extract of leaves Paliasa and determine the effective dose as an antipyretic. Tests were carried out using inducers of fever vaccine Diphtheria Tetanus Pertussis (DPT) 0.2 ml. The antipyretic tests effect is divided into six treatment groups. The first group was given Na CMC 1% and DPT vaccine induced as a negative control, a group of the 2nd given paracetamol as a positive control, all three groups were given Na CMC 1% as the normal control group 4th, 5th, and 6th each given Paliasa leaf ethanol extract at a dose of 100 mg/kg BW, 200 mg/kg BW, and 300 mg/kg BW. Rectal temperature measurements carried out for 6 hours with a 30 minute interval. Temperature measurement data were statistically analyzed using One way ANOVA followed by Duncan test at 95% confidence level. Antipyretic activity test results showed that the ethanol extract of leaves Paliasa have antipyretic activity in male rats and the effective dose is 200 mg/kg BW.